1982
DOI: 10.1111/j.1751-1097.1982.tb04388.x
|View full text |Cite
|
Sign up to set email alerts
|

FORMATION BY HYDROGEN PEROXIDE OR 254 nm RADIATION OF A NEAR‐UV CHROMOPHORE FROM PEPTIDE‐BOUND CYSTEINE

Abstract: Treatment of glutathione or N‐acetylcysteinamide in water with hydrogen peroxide, or with 254 nm radiation together with molecular oxygen, results in the formation of a near‐UV chromophore having maximal absorption at 305 nm. From examination of related compounds, it is apparent that the N‐acylcysteinamide residue is the key element required for generation of the 305 nm chromophore. The structure of this near‐UV chromophore is stable to base but unstable in aqueous acid, is relatively sensitive to oxidation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Reactions [8] and [9] add together to give reaction [I], in good agreement with the usually accepted overall reaction:…”
Section: Kinetic Schemesupporting
confidence: 77%
See 2 more Smart Citations
“…Reactions [8] and [9] add together to give reaction [I], in good agreement with the usually accepted overall reaction:…”
Section: Kinetic Schemesupporting
confidence: 77%
“…But the kinetics of the reaction were not studied. The same observation was obtained when aerated aqueous solutions of GSH were irradiated with a 254 nm radiation (9). From several comparative studies with other thiols in the same conditions, they attributed the absorbance at 305 nm to a product which is formed on the N-acetylcysteinamide (-CONH-CH-CONH2) part I CH2-SH of GSH.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…H202, in turn, was assumed to produce lesions in DNA [Ananthaswamy andEisenstark, 1976, 1977;Ananthaswamy et al, 1979;Hartman, 1986;Hartman andEisenstark, 1978, 1980;Hartman et al, 19793. H202 also may be a photoproduct of cysteine irradiation [Greenberg and Demple, 1986;McCormick et al, 1976McCormick et al, , 1982Owens and Hartman, 19861. We have since found that H202, plus certain wavelengths of NUV, synergistically kill bacteria and phage Hartman and Eisenstark, 1978Hartman et al, 19791. This synergistic action may be the result of NUV conversion of H202 to 0, (superoxide) [Ahmad, 19811, and this action may generate a new NUV photoreceptor [McCormick et al, 19821.…”
Section: Tryptophan Cysteine and Polypeptidesmentioning
confidence: 99%